The effect of tip structure in atomic manipulation : a combined DFT and AFM study. - Jarvis, Samuel Paul (2012)
Non-contact atomic force microscopy allows us to directly probe the interactions between atoms and molecules. When operated in UHV and at low temperatures, a host of experiments, uniquely possible with the technique, can be carried out. The AFM allows us to characterise the forces present on a surface, resolve the atomic structure of molecules, measure the force required to move an atom, and even directly measure molecular pair potentials. Generally speaking, it is the interaction between the outermost tip and surface atoms that we measure. Therefore, in each of these experiments, understanding, or controlling, the tip termination is essential. As NC-AFM experiments become increasingly sophisticated, the combination of experiment and simulation has become critical to understand, and guide the processes at play. In this thesis, I focus on semiconductor surfaces and investigate the role of tip structure in a variety of situations with both DFT simulations and NC-AFM experiments. The clean Si(100) surface consists of rows of dimers, which can be manipulated between two different states using an NC-AFM. In order to understand the manipulation process, detailed DFT and NEB simulations were conducted to examine the energy balance of ideal and defective surfaces, with or without the presence of an AFM tip. We show that an explanation can only be reached when we consider both the AFM tip and variations in the PES caused by surface defects. NC-AFM experiments were also conducted on Si(100):H. We find that on this surface we regularly cultivate chemically passivated, hydrogen-terminated, tip apices which lead to distinct inverted image contrasts in our AFM images. Following a thorough characterisation of the tip apex, we conduct preliminary experiments designed to investigate surface defect structures, and to chemically modify the tip termination. Detailed DFT simulations show that this type of tip engineering, however, critically depends on the larger tip structure, significantly complicating the chances of success. Additionally, we investigate the structure and stability of silicon tip apices using DFT. Even with relatively simple tip structures, we observe complex behaviours, such as tip-dependent dissipation and structural development. These processes provide interesting information regarding tip stability, and commonly observed experimental behaviour. We also model an experiment in which we functionalise the tip apex with a C60 molecule, revealing for the first time that submolecular resolution is possible in the attractive regime.